LEGAL POLITICS IN CRIMINAL LAW POLICIES INREGULATION OF NARCOTICS CRIME IN INDONESIA - Ramadani, Suci; Sinaga, Mhd Mahendra Maskhur; Saragih, Yasmira Mandasari (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Political  Law  in  Criminal  Law  Policy  Against  Arrangement  of Narcotics Crime In Indonesia. The   background of this journal writing is the rampant problem of narcotics abuse has become a national and international problem. Narcotics abuse  can  cause  physical  damage,  mental,  emotional  and  attitudes  in  society.  Various indications indicate that the crime of narcotics is an extraordinary crime is a crime that has  a  large  and  multidimensional  impact  on  life.  In  this  scientific journal,  the  author raises the problem of how the concept of criminal law policy in the prevention of crime and  how  the  criminal  law  policy  on  the  regulation  of  narcotics  crime  in  Indonesia.  In general, this journal is written with the aim that the younger generation and all citizens of  Indonesia  know  what  are  the  policies  of  criminal  law  in  handling  narcotics  cases. This  paper  is  made  with  normative  legal  research  methods  based  on  Law  No.  35  of 2009  on  Narcotics,  law  books,  journals,  and  views  of  jurists  relating  to  the  material under study. Once analyzed The concept of criminal law policy includes criminal policy, criminal  law  policy  and  non-penal  policy  (penal).  Criminal  law  policies  on  the regulation  of  narcotics  crimes  in  Indonesia  include  criminal  liability,  acts  that  are qualified as criminal offenses and criminal sanctions.